Pregnancy outcome following maternal childhood correction of transposition of the great arteries. (18th April 2012) - Stephen, GL; Vause, S; Clarke, B
Abstract : Background: Transposition of the Great Arteries (TGA) is one of the most common cyanotic heart lesions to present in neonates (5-7% of congenital heart disease). Surgical correction of this congenital cardiac abnormality has now improved survival for these children into adulthood. As adults many of these individuals wish to have children of their own. There is potential for pregnancy, with its increased cardiovascular burden, to cause deterioration of maternal cardiac function. And, indeed, poor maternal condition can affect the fetus. Method: We identified all women with TGA who had been managed in the joint obstetric/cardiac clinic at Central Manchester Foundation trust between 2003 and 2011. Data was collected on maternal wellbeing in pregnancy, mode and gestation of delivery, fetal weight and NICU admission. Results: We identified six completed pregnancies. Three of these pregnancies delivered vaginally at term. Three babies were delivered electively by caesarean section. The earliest gestation at delivery was 34 weeks (mean 37.8 weeks). Only the preterm infant was admitted to NICU and there were no adverse maternal outcomes in the postnatal inpatient stay. Discussion: Although we report a small group of patients, our findings of low rates of prematurity and small for gestation babies are consistent with other series which examine this particular cardiac defect. (Ford 2008, Genoni 1999). However, maternal evaluation prior to pregnancy will allow the opportunity to optimise health and ideally improve maternal and fetal outcome.